2‐Ureido‐4‐Pyrimidone‐Based Hydrogels with Multiple Responses. Issue 13 (5th August 2013) - Cui, Jiaxi; Wang, Dapeng; Koynov, Kaloian; del Campo, Aránzazu
Abstract Functionalisation of poly[2‐(dimethylamino)ethyl methacrylate] (a responsive methacrylate) with light‐activatable 2‐ureido‐4‐pyrimidone units allows a supramolecular hydrogel to be obtained that combines temperature, light and pH response with self‐healing properties. Whereas the self‐healing properties of this system were described previously, this report focuses on its response to different external stimuli, which is studied by quartz crystal microbalance analysis of thin films of the material. Reversible collapse with increasing temperature, reversible swelling with decreasing pH and irreversible shrinkage with UV exposure are demonstrated. These three stimuli are combined to have externally gated or tuned responses. Thermo‐induced swelling and shrinkage can be reversibly inhibited by changing the pH and irreversibly regulated by exposure to light of different doses. These materials represent the first general strategy to obtain responsive self‐healing hydrogels in which the response and the self‐healing properties are decoupled from each other and can be tuned independently.